Age-related white matter alterations in children with neurofibromatosis type 1: a diffusion MRI tractography study - Bruckert, Lisa; Travis, Katherine E.; Tam, Lydia T.; Yeom, Kristen W.; Campen, Cynthia J. (Frontiers in Neuroscience, 2025)
Neurofibromatosis type 1 (NF1) is a genetic condition affecting 1 in 3,000 children, often leading to learning challenges, including deficits in attention, executive function, and working memory. While white matter pathways play a crucial role in these cognitive processes, they are not well-characterized in NF1. In this retrospective cohort study, we used diffusion MRI tractography to examine the microstructure of major white matter pathways in 20 children with NF1 (ages 1–18 years) compared to 20 age- and sex-matched controls. An automated approach was used to identify and extract mean diffusivity (MD) and fractional anisotropy (FA) of eight cerebral white matter pathways bilaterally and the anterior and posterior part of the corpus callosum. Compared to controls, children with NF1 had significantly increased MD and significantly decreased FA in multiple white matter pathways including the anterior thalamic radiation, cingulate, uncinate fasciculus, inferior fronto-occipital fasciculus, arcuate fasciculus, and corticospinal tract. Differences in MD and FA remained significant after controlling for intracranial volume. In addition, MD and FA differences between children with NF1 and controls were greater at younger than older ages. These findings have implications for understanding the etiology of the neurocognitive deficits seen in many children with NF1.